Фауна панцирных клещей (Oribatei) почв юга Украины - Фурман, О.К. (Вестник зоологии, 1968)
334 samples are taken from the soil at a depth of 0-40 cm on deep, ordinary and .southern.chernozems of the Odessa region. The author studied the fauna and distribution of Oribatei in soil types and biotopes (idle lands, forest belt, winter wheat, beet). 105 spe-cies of Oribatei are found which are representatives of 62 genera and 42 families. Only some species are numerous and distributed in all the biotopes, but the majority of the species are not numerous and met very seldom. Each soil type and biotope has its own com-plex of dominating species. The greatest number of Oribatei is found in forest belts of deep chenozems, the greatest species diversity in idle lands of ordinary chernozems. .Arable fields are poor in Oribatei.